Proposal for a human capital management framework for remote work - Dextro, Rafael Barty; Manoel (Brazilian Journal of Production Engineering, 2021)
People management is an essential field for companies since individual acting, based on training and quality of working conditions, reflects the organizational performance. Some specific working arrangements, such as remote work or home office mediated by information and communication technologies, require special attention from the perspective of human resources in order to function properly. In this context, the main objective of this study was to identify the overview conditions of remote work, based on the literature and in a single case study, to perform a comparative analysis in a company from the commercial automation sector and understand how people management acts in a home office setting. The methodology used was a qualitative approach and comparative method. This research presented some main results, such as focus and self-discipline are essential qualities to manage remote workers; the advantages and disadvantages perceived by home office workers vary considerably and depend on individual factors like personality and experience; only through active communication and constructive feedback it is possible to avoid the social and professional isolation felt by some remote workers. Nonetheless, the main contribution of this study is the proposition of a framework to guide the establishment of remote work, avoiding part of the problems associated with this work regime.